A ceramic material for new energy vehicle relay and preparation method thereof
By preparing a ceramic material for relays for new energy vehicles, combined with technical means of specific ceramic powders, composite adhesives and chemical coatings, the problem of insufficient arc interruption ability and corrosion resistance of traditional relays in high voltage and high current scenarios is solved, and the problem of insufficient arc interruption ability and corrosion resistance in high voltage and high current scenarios is achieved. The high strength, hardness and density of ceramic materials can meet the high performance needs of new energy vehicle relays.
Patent Information
- Application Number
- CN202410183148.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-02-19
AI Technical Summary
In the mobile scenarios of high voltage and high current DC motors, the arc breaking capacity and volume problems cannot meet the requirements of new energy vehicles. In addition, traditional high-polyester plastic materials age under high temperature, high pressure and high strength, and have poor corrosion resistance. Cannot meet the needs of high-tech products.
A ceramic material for relays for new energy vehicles is adopted. The preparation method includes mixing a specific proportion of the first ceramic powder, the second ceramic powder and a composite adhesive, and obtaining the ceramic material by hot die casting and sintering, and finally chemical plating is carried out to improve the hardness.
By adding components such as Cr2O3, kaolin and SiC, the strength and hardness of the ceramic are improved and the brittleness is reduced; the functionalized carbon nanotubes and microcrystalline wax in the composite binder improve the comprehensive performance of the binder; the plating layer increases the hardness of the ceramic material. , meet the high voltage and high current switching needs of new energy vehicle relays.
Smart Images

Figure CN118026653B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic preparation, and in particular to a ceramic material for a new energy vehicle relay and a preparation method thereof. Background Art
[0002] Environmental protection and resource utilization are advocated all over the world. New energy power batteries are an effective way to solve energy problems. They are first developed in small electric vehicles. At present, they are used to replace fuel engine vehicles in automobile manufacturing. New energy vehicles have more stringent requirements for motor control systems. As a core component of new energy vehicles, motor control is not only related to the performance of the whole vehicle, but also closely related to driving safety. High-performance motor control systems have high requirements on the processing power and safety characteristics of the processor. The voltage of buses is as high as 336VDC, and that of passenger cars is 288VDC, and the motor power is 60kW and 30kW respectively. The current contactors and relays can no longer meet the requirements of this project due to arc breaking ability and volume problems. A new relay that meets the needs of switching high-voltage and high-current DC motors is urgently needed.
[0003] The relay housings on existing electronic and electrical appliances are all made of high-polyester plastics, and their main materials are high-molecular organic materials. They are subject to certain restrictions on high temperature, high pressure, and high strength. They are prone to aging over a long period of time, and cannot meet the needs of existing high-tech products. There are also a large number of harmful substances, and the corrosion resistance is poor, etc., which cannot achieve the electrical connection between the battery and the engine for hybrid vehicles and electric vehicles. New energy vehicle relays are different from ordinary relays. They are required to be able to accurately control the large current that drives the car. At the same time, in order to prevent accidents from causing electric shock to drivers, they also need to have the function of instantly cutting off strong currents. Using ceramic vacuum seals to extinguish arcs is currently the most ideal way, but current ceramic vacuum tubes are all made of ternary ceramic materials, which are brittle, and generally have low strength and hardness.
[0004] Therefore, we proposed a ceramic material for new energy vehicle relays with high strength and hardness. Summary of the invention
[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide a ceramic material for a new energy vehicle relay and a preparation method thereof.
[0006] A ceramic material for a new energy vehicle relay, wherein the raw materials used for preparation include a first ceramic powder, a second ceramic powder, a composite binder and a plating solution coated on the ceramic surface in a weight ratio of 7-10:5-8:2;
[0007] The first ceramic powder comprises the following components in parts by weight:
[0008] 80-85 parts Al2O3, 2-3 parts Cr2O3, 1-2 parts SiO2, 1-2 parts TiO2, 1.5-2 parts kaolin, 0.5-1 parts SiC, with a particle size of 4-5 μm;
[0009] The second ceramic powder comprises the following components in parts by weight:
[0010] 30-40 parts Al2O3, 3-4 parts CuO, 1-2 parts SiO2, 1-2 parts TiO2, 2-3 parts Nb2O5, with a particle size of 3-4μm;
[0011] The plating solution comprises the following components in parts by weight:
[0012] 15-35 parts by weight of nickel sulfate, 20-40 parts by weight of sodium hypophosphite, 10-15 parts by weight of sodium citrate, 3-5 parts by weight of aminoacetic acid, 3-5 parts by weight of succinic acid, 10-15 parts by weight of sodium acetate, and 2-3 parts by weight of lead acetate.
[0013] Furthermore, the composite binder comprises the following components in parts by weight:
[0014] 1-2 parts of functionalized carbon nanotubes, 10-20 parts of paraffin wax, 2-3 parts of microcrystalline wax, 2-3 parts of low-density polyethylene, 0.5-1 parts of stearic acid and 2-3 parts of high-density polyethylene.
[0015] A method for preparing a ceramic material for a new energy vehicle relay comprises the following steps:
[0016] S1: preparing a composite binder, mixing a concentrated H2SO4 solution with an HNO3 solution and adding ethylenediaminetetraacetic acid as a modifier to functionalize carbon nanotubes to obtain functionalized carbon nanotubes, and then mixing 1-2 parts of functionalized carbon nanotubes, 10-20 parts of paraffin wax, 2-3 parts of microcrystalline wax, 2-3 parts of low-density polyethylene, 0.5-1 parts of stearic acid and 2-3 parts of high-density polyethylene as raw materials to obtain a composite binder;
[0017] S2: preparing a first ceramic powder, mixing 80-85 parts of Al2O3, 2-3 parts of Cr2O3, 1-2 parts of SiO2, 1-2 parts of TiO2, 1.5-2 parts of kaolin, and 0.5-1 parts of SiC into a ball mill to obtain a first ceramic powder;
[0018] S3: preparing a second ceramic powder, mixing 30-40 parts of Al2O3, 3-4 parts of CuO, 1-2 parts of SiO2, 1-2 parts of TiO2, and 2-3 parts of Nb2O5, and putting them into a ball mill for ball milling to prepare a second ceramic powder;
[0019] S4: preparing a ceramic material, mixing the first ceramic powder and the second ceramic powder, adding the composite binder and stirring, then adding the mixture into a hot die casting machine mold and high-pressure air injection molding, and finally sintering to obtain a ceramic material;
[0020] S5: coating the ceramic material, using a plating solution to coat the ceramic material, adding pre-treated alumina powder into the electroplating tank at a uniform speed for composite plating after 10-20 minutes of coating, and then cleaning and heat treating to obtain a ceramic material with a coating.
[0021] Furthermore, step S1 includes the following steps:
[0022] S1.1: Mix 40-50 parts by weight of concentrated H2SO4 solution and 20-30 parts by weight of HNO3 solution, add 1-2 parts by weight of ethylenediaminetetraacetic acid, and mix well to obtain a mixed solution;
[0023] S1.2: adding 1-2 parts by weight of carbon nanotubes to the mixed solution, ultrasonically treating for 10-12 hours, centrifuging, washing the precipitate with deionized water until it is neutral, filtering, and drying to obtain functionalized carbon nanotubes;
[0024] S1.3: Weigh 10-20 parts by weight of paraffin wax, melt it at 80-90° C., gradually add 2-3 parts by weight of microcrystalline wax, and mechanically stir it, then add 1-2 parts by weight of functionalized carbon nanotubes, and mechanically stir it for 20-30 minutes to obtain a mixture;
[0025] S1.4: Add the mixture into a closed mixer at 80-85℃ and a stirring speed of 30-35r / min, adjust the temperature to 130-135℃, adjust the speed to 45-50r / min, then add 2-3 parts by weight of low-density polyethylene, react for 15-18 minutes, then add 0.5-1 parts by weight of stearic acid, when the low-density polyethylene is completely dissolved, adjust the temperature to 150-160℃, add 2-3 parts by weight of high-density polyethylene, mix for 1-2h to obtain a composite adhesive.
[0026] Further, step S2 includes the following steps:
[0027] S2.1: Take 80-85 parts by weight of Al2O3, 2-3 parts by weight of Cr2O3, 1-2 parts by weight of SiO2, 1-2 parts by weight of TiO2, 1.5-2 parts by weight of kaolin and 0.5-1 parts by weight of SiC, mix the raw materials and put them into an oven, bake them at 120-150°C for 10-15 minutes to obtain a dried mixture;
[0028] S2.2: Put the mixed material into a ball mill with a material-to-ball ratio of 1:1.5-2, and ball mill for 28-30 hours to obtain a uniform and refined mixed raw material with a particle size of 4-4.8μm to obtain the first ceramic powder.
[0029] Further, step S3 includes the following steps:
[0030] S3.1: Take 30-40 parts by weight of Al2O3, 3-4 parts by weight of CuO, 1-2 parts by weight of SiO2, 1-2 parts by weight of TiO2 and 2-3 parts by weight of Nb2O5, mix the raw materials and put them into an oven, bake them at 120-150°C for 10-15 minutes to obtain a dried mixture;
[0031] S3.2: Put the mixed material into a ball mill with a material-to-ball ratio of 1:1.5-2, and ball mill for 28-30 hours to obtain a uniform and refined mixed raw material with a particle size of 3-4μm to obtain the second ceramic powder.
[0032] Further, step S4 includes the following steps:
[0033] S4.1: mechanically stirring and mixing the first ceramic powder and the second ceramic powder for 2-3 hours, adding a composite binder, and mechanically stirring for 8-10 hours to obtain a ceramic raw material;
[0034] S4.2: adding the ceramic raw material into a hot die casting machine, keeping the temperature at 60-80°C, using a mold and high-pressure air for injection molding at a pressure of 0.6-0.8MPa, and demolding after cooling to obtain a ceramic rough embryo;
[0035] S4.3: Roughly sinter the ceramic to obtain a ceramic material.
[0036] Further, step S5 includes the following steps:
[0037] S5.1: Weigh 15-35 parts by weight of nickel sulfate, 20-40 parts by weight of sodium hypophosphite, 10-15 parts by weight of sodium citrate, 3-5 parts by weight of aminoacetic acid, 3-5 parts by weight of succinic acid, 10-15 parts by weight of sodium acetate, and 2-3 parts by weight of lead acetate, and dissolve them respectively in deionized water to obtain corresponding solutions;
[0038] S5.2: Stir and mix the sodium citrate solution, aminoacetic acid solution and succinic acid, add the nickel sulfate solution during the stirring process, stir vigorously again and add the sodium hypophosphite solution to obtain a mixed solution, mix the sodium acetate solution and the lead acetate solution, add the mixed solution to the mixed solution under sufficient stirring, and adjust the pH to 3.5-5 with dilute sulfuric acid to obtain a plating solution;
[0039] S5.3: 4-10 parts by weight of aluminum oxide powder is pickled with an equal volume of hydrochloric acid for 10-20 seconds, then cleaned with deionized water and dried in an oven at 120-140° C. to obtain pretreated aluminum oxide powder;
[0040] S5.4: placing the metallized ceramic material in a plating tank containing a plating solution for chemical plating, adding the pretreated alumina powder to the plating tank at a uniform speed for composite plating after 10-20 minutes of plating, the adding time is 2-3 minutes, mechanically stirring the powder during the addition, the stirring rate is 250-350r / min, the plating temperature is controlled at 75-95°C, and the plating time is 1-1.5h;
[0041] S5.5: After plating, it is ultrasonically cleaned in deionized water and anhydrous alcohol for 10-15 minutes in turn, and then placed in a vacuum heat treatment furnace for heat treatment after drying, and finally a ceramic material with a coating is obtained.
[0042] Furthermore, the sintering process of step S4.3 is specifically as follows: sintering at 700-800°C for 10-12h, then controlling the temperature at 800-1000°C for sintering for 120-140min, then controlling the temperature at 1000-1400°C for sintering for 120-140min, then controlling the temperature at 1400-1640°C for sintering for 120-140min, and finally controlling the temperature at 1640-1650°C for keeping warm for 60-70min.
[0043] Furthermore, in step S5.5, the heat treatment temperature is 400-410° C. and the time is 1-2 h.
[0044] Compared with the prior art, the present invention has at least the following beneficial effects:
[0045] 1. The present invention adds Cr2O3, kaolin and SiC on the basis of Al2O3 and SiO2, and uses TiO2 as a sintering aid. The addition of TiO2 can form a limited solid solution with Al2O3 that causes crystal distortion, thereby reducing the sintering temperature and promoting the grain refinement of the ceramic, and is beneficial to the densification of sintering. The interaction between the components greatly enhances the strength and hardness of the ceramic and reduces the brittleness.
[0046] 2. The present invention can improve the strength of the wax matrix, reduce the volume shrinkage rate, and refine the grains of the matrix wax when preparing the composite adhesive, thereby improving the comprehensive performance of the composite adhesive. Functionalized carbon nanotubes are added to the adhesive. The functionalized carbon nanotubes can be evenly dispersed in the adhesive matrix. The addition of functionalized carbon nanotubes can effectively improve the crystallinity of the adhesive, thereby improving the strength and shape retention of the ceramic rough blank.
[0047] 3. The particle size of the second ceramic powder of the present invention is smaller than that of the first ceramic powder. When preparing a rough ceramic embryo, the small particles of the ceramic powder can be interspersed and distributed in the remaining pores of the first ceramic powder, thereby reducing the pores between the ceramic powders, improving the density of the ceramic, and increasing the mechanical properties of the ceramic. During the sintering process, the ceramic powder particles are bonded and the grains grow, resulting in the adjacent ceramic powder particles to shrink and reduce the gaps between them, further strengthening the structural strength of the ceramic and improving the hardness of the ceramic.
[0048] 4. The present invention increases the hardness of the ceramic material by chemically plating the ceramic material. After adding alumina powder and performing heat treatment, the coating is transformed from an amorphous coating to a crystalline coating. Ni3P and Ni phases precipitate from the supersaturated solid solution and are dispersed in the coating, which hinders the plastic deformation of the coating and effectively increases the hardness of the coating, thereby increasing the hardness of the ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0050] Figure 1 A flow chart of a ceramic material for a new energy vehicle relay and a preparation method thereof adopted in an embodiment of the present invention. DETAILED DESCRIPTION
[0051] The following is a detailed description of a ceramic material for a new energy vehicle relay and a preparation method thereof provided by the present invention in combination with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0052] Example 1
[0053] A ceramic material for a new energy vehicle relay and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0054] S1: Preparation of composite binder
[0055] S1.1: 40 parts by weight of concentrated H2SO4 solution and 20 parts by weight of HNO3 solution were mixed, and then 1 part by weight of ethylenediaminetetraacetic acid was added, and the mixture was mixed to obtain a mixed solution;
[0056] S1.2: adding 1 part by weight of carbon nanotubes to the mixed solution, ultrasonically treating for 10 hours, centrifuging, washing the precipitate with deionized water until it is neutral, filtering, and drying to obtain functionalized carbon nanotubes;
[0057] S1.3: Weigh 10 parts by weight of paraffin wax, melt it at 80°C, gradually add 2 parts by weight of microcrystalline wax, and stir it mechanically, then add 1 part by weight of functionalized carbon nanotubes, and stir it mechanically for 20 minutes to obtain a mixture;
[0058] S1.4: Add the mixture to a closed mixer at 80°C and a stirring speed of 30 r / min, adjust the temperature to 130°C, adjust the speed to 45 r / min, add 2 parts by weight of low-density polyethylene, react for 15 minutes, add 0.5 parts by weight of stearic acid, adjust the temperature to 150°C when the low-density polyethylene is completely dissolved, add 2 parts by weight of high-density polyethylene, mix for 1 hour, and obtain a composite adhesive;
[0059] S2: Preparation of the first ceramic powder
[0060] S2.1: Take 80 parts by weight of Al2O3, 2 parts by weight of Cr2O3, 1 part by weight of SiO2, 1 part by weight of TiO2, 1.5 parts by weight of kaolin and 0.5 parts by weight of SiC, mix the raw materials and put them into an oven, bake them at 120°C for 10 minutes to obtain a dried mixture;
[0061] S2.2: The mixed material is put into a ball mill with a material-to-ball ratio of 1:1.5, and ball milled for 28 hours to obtain a uniform and refined mixed raw material with a particle size of 4 μm, thereby obtaining a first ceramic powder;
[0062] S3: Preparation of the second ceramic powder
[0063] S3.1: Take 30 parts by weight of Al2O3, 3 parts by weight of CuO, 1 part by weight of SiO2, 1 part by weight of TiO2 and 2 parts by weight of Nb2O5, mix the raw materials and put them into an oven, bake them at 120°C for 10 minutes to obtain a dried mixture;
[0064] S3.2: The mixed material is put into a ball mill with a material-to-ball ratio of 1:1.5, and ball milled for 28 hours to obtain a uniform and refined mixed raw material with a particle size of 3 μm, thereby obtaining a second ceramic powder;
[0065] S4: Preparation of ceramic materials
[0066] S4.1: 7 parts by weight of the first ceramic powder and 5 parts by weight of the second ceramic powder were mechanically stirred and mixed for 2-3 hours, and then 2 parts by weight of the composite binder were added, and mechanically stirred for 8 hours to obtain a ceramic raw material;
[0067] S4.2: adding the ceramic raw material into a hot die casting machine, keeping the temperature at 60°C, using a mold and high-pressure air for injection molding at a pressure of 0.6MPa, and demolding after cooling to obtain a ceramic rough embryo;
[0068] S4.3: sintering the ceramic rough blank at 700°C for 10 hours, then controlling the temperature at 800°C for 120 minutes, then controlling the temperature at 1000°C for 120 minutes, then controlling the temperature at 1400°C for 120 minutes, and finally controlling the temperature at 1640°C for 60 minutes to obtain a ceramic material;
[0069] S5: Coating of ceramic materials
[0070] S5.1: Weigh 15 parts by weight of nickel sulfate, 20 parts by weight of sodium hypophosphite, 10 parts by weight of sodium citrate, 3 parts by weight of aminoacetic acid, 3 parts by weight of succinic acid, 10 parts by weight of sodium acetate, and 2 parts by weight of lead acetate, and dissolve them in deionized water to obtain corresponding solutions;
[0071] S5.2: Stir and mix the sodium citrate solution, aminoacetic acid solution and succinic acid, add the nickel sulfate solution during the stirring process, stir vigorously again and add the sodium hypophosphite solution to obtain a mixed solution, mix the sodium acetate solution and the lead acetate solution, add the mixture to the mixed solution under sufficient stirring, and adjust the pH to 3.5 with dilute sulfuric acid to obtain a plating solution;
[0072] S5.3: 4 parts by weight of aluminum oxide powder was pickled with an equal volume of hydrochloric acid for 10 seconds, then cleaned with deionized water and dried in an oven at 120° C. to obtain pretreated aluminum oxide powder;
[0073] S5.4: Place the metallized ceramic material in a plating tank containing a plating solution for chemical plating. After 10 minutes of plating, add the pretreated alumina powder into the plating tank at a uniform speed for composite plating. The addition time is 2 minutes. The powder is mechanically stirred during the addition. The stirring rate is 250r / min. The plating temperature is controlled at 75°C and the plating time is 1 hour.
[0074] S5.5: After plating, it is ultrasonically cleaned in deionized water and anhydrous alcohol for 10 minutes in turn, and then placed in a vacuum heat treatment furnace for heat treatment at 400°C for 1 hour after drying to finally obtain a ceramic material with a coating.
[0075] Example 2
[0076] A ceramic material for a new energy vehicle relay and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0077] S1: Preparation of composite binder
[0078] S1.1: 50 parts by weight of concentrated H2SO4 solution and 30 parts by weight of HNO3 solution were mixed, and then 2 parts by weight of ethylenediaminetetraacetic acid were added, and the mixture was mixed to obtain a mixed solution;
[0079] S1.2: adding 2 parts by weight of carbon nanotubes to the mixed solution, ultrasonically treating for 10 hours, centrifuging, washing the precipitate with deionized water until it is neutral, filtering, and drying to obtain functionalized carbon nanotubes;
[0080] S1.3: Weigh 20 parts by weight of paraffin wax, melt it at 80°C, gradually add 3 parts by weight of microcrystalline wax, and stir it mechanically, then add 2 parts by weight of functionalized carbon nanotubes, and stir it mechanically for 20 minutes to obtain a mixture;
[0081] S1.4: Add the mixture to a closed mixer at 80°C and a stirring speed of 30 r / min, adjust the temperature to 130°C, adjust the speed to 45 r / min, add 3 parts by weight of low-density polyethylene, react for 15 minutes, add 1 part by weight of stearic acid, adjust the temperature to 150°C when the low-density polyethylene is completely dissolved, add 3 parts by weight of high-density polyethylene, mix for 1 hour, and obtain a composite adhesive;
[0082] S2: Preparation of the first ceramic powder
[0083] S2.1: Take 85 parts by weight of Al2O3, 3 parts by weight of Cr2O3, 2 parts by weight of SiO2, 2 parts by weight of TiO2, 2 parts by weight of kaolin and 1 part by weight of SiC, mix the raw materials and put them into an oven, bake them at 120°C for 10 minutes to obtain a dried mixture;
[0084] S2.2: The mixed material is put into a ball mill with a material-to-ball ratio of 1:2, and ball milled for 28 hours to obtain a uniform and refined mixed raw material with a particle size of 5 μm, thereby obtaining a first ceramic powder;
[0085] S3: Preparation of the second ceramic powder
[0086] S3.1: Take 40 parts by weight of Al2O3, 4 parts by weight of CuO, 2 parts by weight of SiO2, 2 parts by weight of TiO2 and 3 parts by weight of Nb2O5, mix the raw materials and put them into an oven, bake them at 120°C for 10 minutes to obtain a dried mixture;
[0087] S3.2: The mixed material is put into a ball mill with a material-to-ball ratio of 1:2, and ball milled for 28 hours to obtain a uniform and refined mixed raw material with a particle size of 4 μm, thereby obtaining a second ceramic powder;
[0088] S4: Preparation of ceramic materials
[0089] S4.1: 10 parts by weight of the first ceramic powder and 8 parts by weight of the second ceramic powder were mechanically stirred and mixed for 2 hours, and then 2 parts by weight of the composite binder were added, and mechanically stirred for 8 hours to obtain a ceramic raw material;
[0090] S4.2: adding the ceramic raw material into a hot die casting machine, keeping the temperature at 60°C, using a mold and high-pressure air for injection molding at a pressure of 0.6MPa, and demolding after cooling to obtain a ceramic rough embryo;
[0091] S4.3: sintering the ceramic rough blank at 700°C for 10 hours, then controlling the temperature at 800°C for 120 minutes, then controlling the temperature at 1000°C for 120 minutes, then controlling the temperature at 1400°C for 120 minutes, and finally controlling the temperature at 1640°C for 60 minutes to obtain a ceramic material;
[0092] S4: Plating ceramic materials
[0093] S5.1: Weigh 35 parts by weight of nickel sulfate, 40 parts by weight of sodium hypophosphite, 15 parts by weight of sodium citrate, 5 parts by weight of aminoacetic acid, 5 parts by weight of succinic acid, 15 parts by weight of sodium acetate, and 3 parts by weight of lead acetate, and dissolve them respectively in deionized water to obtain corresponding solutions;
[0094] S5.2: Stir and mix the sodium citrate solution, aminoacetic acid solution and succinic acid, add the nickel sulfate solution during the stirring process, stir vigorously again and add the sodium hypophosphite solution to obtain a mixed solution, mix the sodium acetate solution and the lead acetate solution, add the mixed solution to the mixed solution under sufficient stirring, and adjust the pH to 3.5-5 with dilute sulfuric acid to obtain a plating solution;
[0095] S5.3: 10 parts by weight of aluminum oxide powder was pickled with an equal volume of hydrochloric acid for 10 seconds, then cleaned with deionized water and dried in an oven at 120° C. to obtain pretreated aluminum oxide powder;
[0096] S5.4: Place the metallized ceramic material in a plating tank containing a plating solution for chemical plating. After 10 minutes of plating, add the pretreated alumina powder into the plating tank at a uniform speed for composite plating. The addition time is 2 minutes. The powder is mechanically stirred during the addition. The stirring rate is 250r / min. The plating temperature is controlled at 75°C and the plating time is 1 hour.
[0097] S5.5: After plating, it is ultrasonically cleaned in deionized water and anhydrous alcohol for 10 minutes in turn, and then placed in a vacuum heat treatment furnace for heat treatment at 400°C for 1 hour after drying to finally obtain a ceramic material with a coating.
[0098] Example 3
[0099] A ceramic material for a new energy vehicle relay and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0100] S1: Preparation of composite binder
[0101] S1.1: 40 parts by weight of concentrated H2SO4 solution and 20 parts by weight of HNO3 solution were mixed, and then 1 part by weight of ethylenediaminetetraacetic acid was added, and the mixture was mixed to obtain a mixed solution;
[0102] S1.2: adding 1 part by weight of carbon nanotubes to the mixed solution, ultrasonically treating for 12 hours, centrifuging, washing the precipitate with deionized water until it is neutral, filtering, and drying to obtain functionalized carbon nanotubes;
[0103] S1.3: Weigh 10 parts by weight of paraffin wax, melt it at 90° C., gradually add 2 parts by weight of microcrystalline wax, and stir it mechanically, then add 1 part by weight of functionalized carbon nanotubes, and stir it mechanically for 30 minutes to obtain a mixture;
[0104] S1.4: Add the mixture to a closed mixer at 85°C and a stirring speed of 35 r / min, adjust the temperature to 135°C, adjust the speed to 50 r / min, add 2-3 parts by weight of low-density polyethylene, react for 18 minutes, add 0.5 parts by weight of stearic acid, adjust the temperature to 160°C when the low-density polyethylene is completely dissolved, add 2 parts by weight of high-density polyethylene, mix for 2 hours, and obtain a composite adhesive;
[0105] S2: Preparation of the first ceramic powder
[0106] S2.1: Take 80 parts by weight of Al2O3, 2 parts by weight of Cr2O3, 1 part by weight of SiO2, 1 part by weight of TiO2, 1.5 parts by weight of kaolin and 0.5 parts by weight of SiC, mix the raw materials and put them into an oven, bake them at 150°C for 15 minutes to obtain a dried mixture;
[0107] S2.2: The mixed material is put into a ball mill with a material-to-ball ratio of 1:1.5, and ball milled for 30 hours to obtain a uniform and refined mixed raw material with a particle size of 4 μm, thereby obtaining a first ceramic powder;
[0108] S3: Preparation of the second ceramic powder
[0109] S3.1: Take 30 parts by weight of Al2O3, 3 parts by weight of CuO, 1 part by weight of SiO2, 1 part by weight of TiO2 and 2 parts by weight of Nb2O5, mix the raw materials and put them into an oven, bake them at 150°C for 15 minutes to obtain a dried mixture;
[0110] S3.2: The mixed material is put into a ball mill with a material-to-ball ratio of 1:1.5, and ball milled for 30 hours to obtain a uniform and refined mixed raw material with a particle size of 3 μm, thereby obtaining a second ceramic powder;
[0111] S4: Preparation of ceramic materials
[0112] S4.1: mechanically stirring and mixing the first ceramic powder and the second ceramic powder for 3 hours, adding a composite binder, and mechanically stirring for 10 hours to obtain a ceramic raw material;
[0113] S4.2: adding the ceramic raw material into a hot die casting machine, keeping the temperature at 80°C, using a mold and high-pressure air for injection molding at a pressure of 0.8MPa, and demolding after cooling to obtain a ceramic rough embryo;
[0114] S4.3: sintering the ceramic rough blank at 800°C for 12 hours, then controlling the temperature at 1000°C for 140 minutes, then controlling the temperature at 1400°C for 140 minutes, then controlling the temperature at 1640°C for 140 minutes, and finally controlling the temperature at 1650°C for 70 minutes to obtain a ceramic material;
[0115] S5: Coating of ceramic materials
[0116] S5.1: Weigh 15 parts by weight of nickel sulfate, 20 parts by weight of sodium hypophosphite, 10 parts by weight of sodium citrate, 3 parts by weight of aminoacetic acid, 3 parts by weight of succinic acid, 10 parts by weight of sodium acetate, and 2 parts by weight of lead acetate, and dissolve them in deionized water to obtain corresponding solutions;
[0117] S5.2: Stir and mix the sodium citrate solution, aminoacetic acid solution and succinic acid, add the nickel sulfate solution during the stirring process, stir vigorously again and add the sodium hypophosphite solution to obtain a mixed solution, mix the sodium acetate solution and the lead acetate solution, add the mixture to the mixed solution under sufficient stirring, and adjust the pH to 3.5 with dilute sulfuric acid to obtain a plating solution;
[0118] S5.3: 4-10 parts by weight of aluminum oxide powder is pickled with an equal volume of hydrochloric acid for 20 seconds, then cleaned with deionized water and dried in an oven at 140° C. to obtain pretreated aluminum oxide powder;
[0119] S5.4: Place the metallized ceramic material in a plating tank containing a plating solution for chemical plating. After 20 minutes of plating, add the pretreated alumina powder into the plating tank at a uniform speed for composite plating. The adding time is 3 minutes. The powder is mechanically stirred during the addition. The stirring rate is 350 r / min. The plating temperature is controlled at 95°C and the plating time is 1.5 hours.
[0120] S5.5: After plating, it is ultrasonically cleaned in deionized water and anhydrous alcohol for 15 minutes in turn, and then placed in a vacuum heat treatment furnace for heat treatment at 410°C for 2 hours after drying to finally obtain a ceramic material with a coating.
[0121] Comparative Example 1
[0122] Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 is 95% alumina ceramic, recorded as Comparative Example 1.
[0123] The ceramic materials prepared in Example 1, Example 2, and Example 3 and the alumina ceramics of Comparative Example 1 were tested for performance, and the test was conducted twice in parallel. The test results are shown in Table 1 below:
[0124] Table 1. Performance comparison table of examples and comparative examples
[0125]
[0126] It can be seen from Table 1 that the flexural strength and hardness of the embodiment are higher than those of the comparative example, which indicates that the preparation process of the embodiment can improve the strength and hardness of the ceramic material, so that the ceramic material has excellent strength and hardness.
[0127] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A ceramic material for a new energy vehicle relay, characterized in that: The raw materials used for the preparation include a first ceramic powder, a second ceramic powder, and a composite binder in a weight ratio of 7-10:5-8:2, and a ceramic material is plated on the ceramic surface using a plating solution. After 10-20 minutes of plating, a pre-treated alumina powder is uniformly added into the electroplating tank for composite plating to obtain a ceramic material; The first ceramic powder comprises the following components in parts by weight: 80-85 parts Al2O3, 2-3 parts Cr2O3, 1-2 parts SiO2, 1-2 parts TiO2, 1.5-2 parts kaolin, 0.5-1 parts SiC, with a particle size of 4-5 μm; The second ceramic powder comprises the following components in parts by weight: 30-40 parts Al2O3, 3-4 parts CuO, 1-2 parts SiO2, 1-2 parts TiO2, 2-3 parts Nb2O5, with a particle size of 3-4μm; The plating solution comprises the following components in parts by weight: 15-35 parts by weight of nickel sulfate, 20-40 parts by weight of sodium hypophosphite, 10-15 parts by weight of sodium citrate, 3-5 parts by weight of aminoacetic acid, 3-5 parts by weight of succinic acid, 10-15 parts by weight of sodium acetate, and 2-3 parts by weight of lead acetate.
2. A ceramic material for new energy vehicle relay according to claim 1, characterized in that: The composite binder comprises the following components in parts by weight: 1-2 parts of functionalized carbon nanotubes, 10-20 parts of paraffin wax, 2-3 parts of microcrystalline wax, 2-3 parts of low-density polyethylene, 0.5-1 parts of stearic acid and 2-3 parts of high-density polyethylene.
3. A method for preparing a ceramic material for a new energy vehicle relay, characterized in that: The steps include: S1: preparing a composite binder, mixing a concentrated H2SO4 solution with an HNO3 solution and adding ethylenediaminetetraacetic acid as a modifier to functionalize carbon nanotubes to obtain functionalized carbon nanotubes, and then mixing 1-2 parts of functionalized carbon nanotubes, 10-20 parts of paraffin wax, 2-3 parts of microcrystalline wax, 2-3 parts of low-density polyethylene, 0.5-1 parts of stearic acid and 2-3 parts of high-density polyethylene as raw materials to obtain a composite binder; S2: preparing a first ceramic powder, mixing 80-85 parts of Al2O3, 2-3 parts of Cr2O3, 1-2 parts of SiO2, 1-2 parts of TiO2, 1.5-2 parts of kaolin, and 0.5-1 parts of SiC into a ball mill to obtain a first ceramic powder with a particle size of 4-5 μm; S3: preparing a second ceramic powder, mixing 30-40 parts of Al2O3, 3-4 parts of CuO, 1-2 parts of SiO2, 1-2 parts of TiO2, and 2-3 parts of Nb2O5, and putting them into a ball mill for ball milling to prepare a second ceramic powder with a particle size of 3-4 μm; S4: preparing a ceramic material, mixing the first ceramic powder and the second ceramic powder, adding the composite binder and stirring, then adding the mixture into a hot die casting machine mold and high-pressure air injection molding, and finally sintering to obtain a ceramic material; S5: coating the ceramic material, preparing a plating solution with 15-35 parts by weight of nickel sulfate, 20-40 parts by weight of sodium hypophosphite, 10-15 parts by weight of sodium citrate, 3-5 parts by weight of aminoacetic acid, 3-5 parts by weight of succinic acid, 10-15 parts by weight of sodium acetate, and 2-3 parts by weight of lead acetate as raw materials, coating the ceramic material with the plating solution, and after 10-20 minutes of coating, uniformly adding pretreated alumina powder into the electroplating tank for composite plating, and then cleaning and heat treating to obtain a ceramic material with a coating.
4. The method for preparing a ceramic material for a new energy vehicle relay according to claim 3, characterized in that: Step S1 includes the following steps: S1.1: Mix 40-50 parts by weight of concentrated H2SO4 solution and 20-30 parts by weight of HNO3 solution, add 1-2 parts by weight of ethylenediaminetetraacetic acid, and mix well to obtain a mixed solution; S1.2: adding 1-2 parts by weight of carbon nanotubes to the mixed solution, ultrasonically treating for 10-12 hours, centrifuging, washing the precipitate with deionized water until it is neutral, filtering, and drying to obtain functionalized carbon nanotubes; S1.3: Weigh 10-20 parts by weight of paraffin wax, melt it at 80-90° C., gradually add 2-3 parts by weight of microcrystalline wax, and mechanically stir it, then add 1-2 parts by weight of functionalized carbon nanotubes, and mechanically stir it for 20-30 minutes to obtain a mixture; S1.4: Add the mixture into a closed mixer at 80-85℃ and a stirring speed of 30-35r / min, adjust the temperature to 130-135℃, adjust the speed to 45-50r / min, then add 2-3 parts by weight of low-density polyethylene, react for 15-18 minutes, then add 0.5-1 parts by weight of stearic acid, when the low-density polyethylene is completely dissolved, adjust the temperature to 150-160℃, add 2-3 parts by weight of high-density polyethylene, mix for 1-2h to obtain a composite adhesive.
5. The method for preparing a ceramic material for a new energy vehicle relay according to claim 4, characterized in that: Step S2 includes the following steps: S2.1: Take 80-85 parts by weight of Al2O3, 2-3 parts by weight of Cr2O3, 1-2 parts by weight of SiO2, 1-2 parts by weight of TiO2, 1.5-2 parts by weight of kaolin and 0.5-1 parts by weight of SiC, mix the raw materials and put them into an oven, bake them at 120-150°C for 10-15 minutes to obtain a dried mixture; S2.2: Put the mixed material into a ball mill with a material-to-ball ratio of 1:1.5-2, and ball mill for 28-30 hours to obtain a uniform and refined mixed raw material with a particle size of 4-5μm to obtain the first ceramic powder.
6. The method for preparing a ceramic material for a new energy vehicle relay according to claim 5, characterized in that: Step S3 includes the following steps: S3.1: Take 30-40 parts by weight of Al2O3, 3-4 parts by weight of CuO, 1-2 parts by weight of SiO2, 1-2 parts by weight of TiO2 and 2-3 parts by weight of Nb2O5, mix the raw materials and put them into an oven, bake them at 120-150°C for 10-15 minutes to obtain a dried mixture; S3.2: Put the mixed material into a ball mill with a material-to-ball ratio of 1:1.5-2, and ball mill for 28 hours to obtain a uniform and refined mixed raw material with a particle size of 3-4μm to obtain the second ceramic powder.
7. The method for preparing a ceramic material for a new energy vehicle relay according to claim 6, characterized in that: Step S4 includes the following steps: S4.1: mechanically stirring and mixing the first ceramic powder and the second ceramic powder for 2-3 hours, adding a composite binder, and mechanically stirring for 8-10 hours to obtain a ceramic raw material; S4.2: adding the ceramic raw material into a hot die casting machine, keeping the temperature at 60-80°C, using a mold and high-pressure air for injection molding at a pressure of 0.6-0.8MPa, and demolding after cooling to obtain a ceramic rough embryo; S4.3: Roughly sinter the ceramic to obtain a ceramic material.
8. The method for preparing a ceramic material for a new energy vehicle relay according to claim 6, characterized in that: Step S5 includes the following steps: S5.1: Weigh 15-35 parts by weight of nickel sulfate, 20-40 parts by weight of sodium hypophosphite, 10-15 parts by weight of sodium citrate, 3-5 parts by weight of aminoacetic acid, 3-5 parts by weight of succinic acid, 10-15 parts by weight of sodium acetate, and 2-3 parts by weight of lead acetate, and dissolve them respectively in deionized water to obtain corresponding solutions; S5.2: Stir and mix the sodium citrate solution, aminoacetic acid solution and succinic acid, add the nickel sulfate solution during the stirring process, stir vigorously again and add the sodium hypophosphite solution to obtain a mixed solution, mix the sodium acetate solution and the lead acetate solution, add the mixed solution to the mixed solution under sufficient stirring, and adjust the pH to 3.5-5 with dilute sulfuric acid to obtain a plating solution; S5.3: 4-10 parts by weight of aluminum oxide powder is pickled with an equal volume of hydrochloric acid for 10-20 seconds, then cleaned with deionized water and dried in an oven at 120-140° C. to obtain pretreated aluminum oxide powder; S5.4: placing the metallized ceramic material in a plating tank containing a plating solution for chemical plating, adding the pretreated alumina powder to the plating tank at a uniform speed for composite plating after 10-20 minutes of plating, the adding time is 2-3 minutes, mechanically stirring the powder during the addition, the stirring rate is 250-350r / min, the plating temperature is controlled at 75-95°C, and the plating time is 1-1.5h; S5.5: After plating, it is ultrasonically cleaned in deionized water and anhydrous alcohol for 10-15 minutes in turn, and then placed in a vacuum heat treatment furnace for heat treatment after drying, and finally a ceramic material with a coating is obtained.
9. The method for preparing a ceramic material for a new energy vehicle relay according to claim 7, characterized in that: The sintering process of step S4.3 is specifically as follows: sinter at 700-800℃ for 10-12h, then control the temperature at 800-1000℃ for sintering for 120-140min, then control the temperature at 1000-1400℃ for sintering for 120-140min, then control the temperature at 1400-1640℃ for sintering for 120-140min, and finally control the temperature at 1640-1650℃ for insulation for 60-70min.
10. The method for preparing a ceramic material for a new energy vehicle relay according to claim 8, characterized in that: In step S5.5, the heat treatment temperature is 400-410°C and the time is 1-2h.
Citation Information
Patent Citations
Method for preparing eutectic ceramics
CN101445361A
Negative temperature coefficient polymer composite material for temperature sensing cable and preparation method
CN101654530A